Diagnosis and Treatment of Ureteral Endometriosis: Study Of 23 Cases - Mu, Dawei; Li, Xuesong; Zhou, Gaobiao; Guo, Heqing (Urology Journal, 2014)
Purpose: To describe our experience in the diagnosis and treatment of 23 patients with ureteral endometriosis. Materials and Methods: We performed a retrospective analysis of 23 cases of ureteral endometriosis with histopathological results from 2002 to 2011. Results: In patients with ureteral endometriosis, 23 cases were diagnosed by ultrasound, 21 by intravenous urography, 11 by retrograde urography, 16 by computed tomography, and 8 with magnetic resonance imaging. All cases were treated by operative treatment. The treatments included ureterolysis in 3 cases, partial ureteral resection and ureteroneocystostomy in 6 cases, partial ureteral resection and end-to-end ureteral anastomosis in 12 cases, and endoscopic resection of ureteral endometriosis lesion in 2 cases. All of the pathologic examination results were endometriosis. Conclusion: Our findings suggest that surgery is an effective treatment option in most patients with ureteral endometriosis exhibiting mild or moderate to severe hydronephrosis. The type of technique depends on the location and depth of the lesion.